The Effect of Audiobook on Reading Comprehension of the Eleventh Grade Students of SMA Negeri 2 Buru - Abd. Rahman; Ibnu Hajar (ELT Worldwide: Journal of English Language Teaching, 2020)
ABSTRACTThe audiobook does not only involves multiple senses of the students, but also the inclusion of its speech, helping them to improve their comprehension. This study sought to investigate the effects' of audiobook on students' reading comprehension, and to find out students' interest in audiobooks on the teaching of reading. The mixed method called the Quan-qual model applied at this study. Some sixty eleventh-grade students participated, and data were collected by employing reading comprehension tests and questionnaires (open-ended questions). The quantitative data analyzed using paired and independent sample t-test through SPSS 20 Version, and the qualitative data analyzed through an open-coding technique. The use of audiobook was more effective than the non-audiobook. It is proven by the comparison of the mean score from both of  the groups which (68.00 ˃ 48.80). The p-value in the post-test is .000, and the level of significance is α 0.05, the p-value is smaller than α (.000<0.05).  The hypothesis testing found that t-value = 14.699 was higher than t-table = 2.045 (p=.000, df=29); it means that Ha was accepted, and Ho was rejected. Another, the students are interested in using audiobooks because it stimulating, challenging, available, powerful and innovative in the reading activity. Keywords: Audiobook, Reading Comprehension, Student Interest.